Documenting graffiti culture:: an evolution of content - Perroncel, Tristana (Street Art & Urban Creativity, 2018)
Since its early years, graffiti has been documented with photographs and videos, showing legal and illegal activities in the streets. The most famous photographer of this time will always remain Martha Cooper, who still runs her photographer activities and is invited to the most important events of the graffiti culture in the world. In the mid-seventies, the first digital camera was coming out leading towards a real revolution in filming and photography. Technology has then developed extensively and cameras with higher resolution allowed graffiti writers and audio-visual artists to produce work of higher quality and with new visual perspectives. This progression in time has changed the way of documenting graffiti culture and has expanded its possibilities in terms of visual content, thanks to the democratization of technologies and its improvements. I have photographed and filmed a few groups of graffiti writers, which gave me insight into this culture. This essay wishes to introduce some thoughts on this subject and open a longer discussion concerning the importance of audio-visual material for graffiti as an ephemeral art form.